Revealing the impact of fintech on energy saving and carbon reduction innovation - Yu, Bingbing; Zhao, Fuming (Frontiers in Environmental Science, 2025)
Financial technology (fintech) is the application of cutting-edge technology in the financial sector, with potential value for the low-carbon economic transition. In the context of intensified global warming, using fintech to promote energy saving and carbon reduction innovation (ESCRI) presents a thought-provoking practical challenge. This study utilizes data from 30 Chinese provinces spanning 2011 to 2022 to empirically examine whether fintech can improve ESCRI. Results revealed that first, fintech significantly promotes ESCRI, a conclusion supported by a series of robustness tests. Second, the main pathways through which fintech affects ESCRI are industrial scale, investment expansion, and R&D expenditure. Third, in provinces with poor environmental quality, lagging industrial upgrading, and in the central and western regions, fintech’s positive effect on ESCRI is more significant. Fourth, fintech demonstrates a significant impact on reducing carbon emissions. The results of this study provide strong evidence for actively utilizing fintech to promote ESCRI on a global scale and offer empirical insight into the underlying logic of green and low-carbon development.